Strong Evidence of Highly Pathogenic and Low Pathogenic Avian Influenza Viruses in Domestic Poultry in Iraq (Medico Legal Update, 2020)
Background: Avian influenza is very important contagious disease caused by Avian Influenza A viruseswhich continue to pose real threats for both human and animal. The virus subdivided into many HA and NAsubtypes, some of them are highly pathogenic while others are low pathogenic for poultry.Method: Nasal swabs or fresh tracheal swabs in case of dead birds were taken from 417of chicken farmsand flocks besides to 689 of local poultry that grew in the backyards all over Iraq to detect and identify viralsubtypes.Results: Avian influenza viruses were observed in 7.04% of commercial chicken farms and in 4.93% oflocal poultry that growing in the backyards at Iraq; following subtypes were recorded: H9N2, H5N1, H7N9,H5N8 and H5N2. Subtype H9N2 is the prevalent type, all infections with H5N1, H5N8 and 28.57% of H7N9subtypes were highly pathogenic; 100% of infections with H9N2, H5N2 and 71.42% of H7N9 appeared aslow pathogenic.Conclusions: According to the author’s knowledge, the present study is first study recordedavian Influenzavirus subtypes: H5N1, H7N9, H5N8 and H5N2 in domestic birds at Iraq.